Enhancing 21st-Century Learning Skills in Early Childhood through a Local Wisdom-Integrated Science, Technology, Engineering, Arts, and Mathematics (STEAM) Learning Package to Support Sustainable Development Goals (SDGs): A Bibliometric and Mixed-Methods Study - Sudthiporn Chatathicoon; Sampan Thinwiangthong; Duangmanee Leelalawan; Thawee Sranamkam; Chuanchuen Malila; Supasit Khonyai; Naphaporn Woranetsudathip; Niyom Wongpongkham (ASEAN Journal of Educational Research and Technology, 2026)
This study examined the effect of a local wisdom-integrated science, technology, engineering, arts, and mathematics (STEAM) learning package on 21st-century learning skills in early childhood and positioned the topic within Sustainable Development Goals (SDGs)-oriented education through bibliometric mapping. 40 early childhood students participated in the “Rice and Farmers” learning unit using the I-WISDOM package. Quantitative data were analyzed using dependent sample t-tests and Cohen’s effect size, while qualitative data were interpreted through analytic description. The findings showed significant improvement in creativity, problem solving, communication, and collaboration. Students also demonstrated appreciation of rice farming as local wisdom. The study supports quality education, cultural sustainability, and early skill development through STEAM-based learning.